Influence of ZrO2 content on the mechanical, electrical, and microstructural characteristics of La1-xZrxCo1−yMnyO3 perovskites for IT-SOFC cathodes - Md. Abu Daud; Robel Ahmed; Md. Nurul Islam; Md Mahadi Hassan Parvez; Md. Shofiqul Islam; M. A. Gafur; Aninda Nafis Ahmed (PLoS ONE, 2025)
In this research, the doping effects of ZrO2 and MnO2 on La1-xZrxCo1−yMnyO3 cathode were investigated in terms of physical, mechanical and electrical properties. The amount of ZrO2 was varied by 5wt%, 10wt%, and 15wt% for different compositions of the composites and MnO2 was varied accordingly. The composite cathode is prepared to enhance the structural and functional properties of La1-xZrxCo1−yMnyO3 composites by varying ZrO2 doping levels, optimizing their suitability for high-performance applications through detailed material characterization in powder and pellet form, followed by calcination at 1000°C and sintering at 1200°C. The final sintered composites were then examined by SEM-EDX, XRD, and AFM. Investigations were also conducted on density, porosity, compressive strength, thermal expansion coefficient (TEC), electronic conductivity, and diametral tensile strength (DTS). SEM and EDX shows both imaging and chemical analysis of the composites which indicates the results of reactions during sintering. XRD indicates that significant structural change had been taken place with the addition of ZrO2. These defects in perovskite structure will increase the ionic and electronic conductivity of the composites. The highest value of DTS, compressive strength was obtained for 15LZCM sample and lowest value of DTS, and compressive strength was observed for the 5LZCM sample. Some properties like microhardness, thermal expansion, and electrical conductivity were also determined. XRD analysis shows ZrO2 doping caused transformation of the perovskite structure and the leading crystal system was monoclinic (P 1 21/c1). SEM shows the porous microstructure of the perovskite oxide. AFM reveals the addition of the ZrO2 decreasing roughness; the rms roughness of 5LZCM was 61.46 nm but the rms roughness was 37.12 nm for 15LZCM.